Auditory and Audiovisual Close Shadowing in Post-Lingually Deaf Cochlear-Implanted Patients and Normal-Hearing Elderly Adults. Issue 1 (January 2018) - Scarbel, Lucie; Beautemps, Denis; Schwartz, Jean-Luc; Sato, Marc
Abstract : Objectives: The goal of this study was to determine the effect of auditory deprivation and age-related speech decline on perceptuo–motor abilities during speech processing in post-lingually deaf cochlear-implanted participants and in normal-hearing elderly (NHE) participants. Design: A close-shadowing experiment was carried out on 10 cochlear-implanted patients and on 10 NHE participants, with two groups of normal-hearing young participants as controls. To this end, participants had to categorize auditory and audiovisual syllables as quickly as possible, either manually or orally. Reaction times and percentages of correct responses were compared depending on response modes, stimulus modalities, and syllables. Results: Responses of cochlear-implanted subjects were globally slower and less accurate than those of both young and elderly normal-hearing people. Adding the visual modality was found to enhance performance for cochlear-implanted patients, whereas no significant effect was obtained for the NHE group. Critically, oral responses were faster than manual ones for all groups. In addition, for NHE participants, manual responses were more accurate than oral responses, as was the case for normal-hearing young participants when presented with noisy speech stimuli. Conclusions: Faster reaction times were observed for oral than for manual responses in all groups, suggesting that perceptuo–motor relationships were somewhat successfully functional after cochlear implantation and remain efficient in the NHE group. These results are in agreement with recent perceptuo–motor theories of speech perception. They are also supported by the theoretical assumption that implicit motor knowledge and motor representations partly constrain auditory speech processing. In this framework, oral responses would have been generated at an earlier stage of a sensorimotor loop, whereas manual responses would appear late, leading to slower but more accurate responses. The difference between oral and manual responses suggests that the perceptuo–motor loop is still effective for NHE subjects and also for cochlear-implanted participants, despite degraded global performance.